168 Developing future lifesavers & beyond. Improving CPR outreach through medical students. (16th November 2020) - Vyshnavi, Ankathi; Bandi, Varun Kumar; Pusuluri, Satyanayana Murthy
Abstract : Introduction: Timely and effective Cardiopulmonary Resuscitation (CPR) can increase the survival rates by 3times. Bystander CPR rate in India is very dismal as 1.3%.1 The present study aims to training all medical undergraduates in Basic Life support(BLS) for delivering effective CPR and Increasing` CPR outreach by training the community. Methodology: Students were divided into groups of 30, had three instructors, with a mannequin for every 3 students. Students were given video lectures, followed by hands-on training. Students were evaluated about confidence, likelihood of peer teaching, and implementation. The medical students were trained in first year, and again during Internship. A second-tier was proposed from May 2020, where trained undergraduates will be instructed to teach the CPR methods to a minimum of 5 people from the community using home-made mannequin. The program has been now temporarily halted due to pandemic. Results: Till date, 1950 undergraduates have been trained, and all 750 students in campus are BLS-CPR providers. The confidence to perform independent CPR after the training was about 64.2%, with internees being more confident (81.3%). Likelihood of implementing CPR was 40.9%, with those confident more likely to implement (54.3%). Likelihood of peer teaching was 22.9% overall, which was only 7% among those who were not confident. There was a significant difference among the above parameters between those confident and not confident after training (p<0.001). The program produces 150 new CPR providers per year, and second phase could add more than 3750 providers in the community, with 750 people being added each year. Conclusion: We proposed to empower future lifesavers who are young and enthusiastic about learning new skills and also to impart them to others there by increasing the number of first responders in the community.